Transglutaminase 2 strongly binds to an extracellular matrix component other than fibronectin via its second C‐terminal beta‐barrel domain. (11th October 2016) - Stamnaes, Jorunn; Cardoso, Inês; Iversen, Rasmus; Sollid, Ludvig M.
Abstract : Transglutaminase 2 (TG2) is a ubiquitous crosslinking enzyme present in both intra‐ and extracellular in many cell types and tissues. TG2 is upregulated upon cellular stress or injury, and extracellular TG2 is implicated in several human diseases, including celiac disease. However, incomplete knowledge about extracellular TG2 biology limits our understanding of how TG2 is involved in disease. Here, we demonstrate that binding of TG2 to the ECM of small intestinal tissue sections is the sum of binding to fibronectin (FN) via its N‐terminal domain and binding to an abundant, novel extracellular matrix (ECM) interaction partner via its second C‐terminal beta‐barrel domain. The latter interaction dominates and gives rise to the characteristic reticular staining pattern of extracellular TG2. Of relevance for celiac disease, we show that self‐multimerized TG2 does not efficiently deposit in the intestinal ECM, and TG2 complexes may thus become free‐floating antigens in tissues in contrast to monomeric TG2 that would readily become sequestered by the ECM. Upon injection of monoclonal antibody targeting the FN‐binding site, we observe antibody deposition on extracellular TG2 in cryosections, suggesting that the FN‐binding site of TG2 is exposed in vivo . This would explain how and why celiac autoantibodies recognizing the FN‐binding site of TG2 can bind TG2 in vitro, in situ as well as in vivo . Abstract : Extracellular matrix (ECM)‐bound transglutaminase 2 (TG2) is the target of celiac disease autoantibodies. TG2 binds fibronectin (FN) via its N‐terminal domain masking epitope 1. We demonstrate that TG2 also binds abundantly to the ECM via its C2‐domain. This explains how ECM‐bound TG2 is recognized by epitope 1 antibodies and changes our perception of TG2 in the ECM.